Gut Microbiota–Medication Interaction in Rheumatic Diseases - Zhang, Lingshu; Chu, Cong-Qiu (Frontiers in Immunology, 2021)
Besides contribution to the development of rheumatic diseases, gut microbiota interact with anti-rheumatic drugs. Intestinal microbiota can directly metabolize many drugs and indirectly change drug metabolism through a complex multi-dimensional interaction with the host thus affecting individual response to drug therapy and adverse effects. The focus of the current review is to address recent advances and important progress in our understanding of how gut microbiota interact with anti-rheumatic drugs and provide perspectives on promoting precision treatment, drug discovery and better therapy for rheumatic diseases.